Synthesis, Characterization and Biocompatibility of Maltodextrin-coated Cadmium Sulfide Quantum Dots in Experimental Models - Rodríguez-López Anahi; Ayala-Calvillo Erick; Rodríguez-Fragoso Patricia; Gerardo González De la Cruz; Lourdes Rodríguez-Fragoso (Recent Progress in Science and Technology Vol. 1, 2023)
Semiconductor Quantum dots (QDs) have gained quite a bit of popularity due to their characteristics and widespread application in biological and biomedical research. However, these very same features present further difficulties in comprehending, predicting, and controlling possible adverse health consequences after exposure. These past few years, QDs have rapidly become popular and novel tools for theragnostic purposes; their use entails the concomitant safety studies. Cadmium and selenium, which are the main components in the majority of quantum dots, are known to be acutely and chronically toxic to cells and organisms, but protecting the core of nanoparticles can, to some degree, control toxicity related to cadmium and selenium leakage. Our research has shown that CdS-maltodextrin (CdS-MDx) QDs are biocompatible and nontoxic to cells and animals. However, QDs can still induce embryotoxic effects. This study successfully synthesized and characterized maltodextrin coated cadmium sulfide semiconductor nanoparticles (CdS-MDx QDs) and the results showed that, in low concentrations (4.92 and 6.56 nM), these lightly increased the number of HepG2 cells. We also observed a reduction in MDA-MB-231 cells under concentrations higher than 4.92 nM in a dose-response manner, while Caco-2 cells significantly increased starting at 1.64 nM. CdS-MDx QDs induced cell death by apoptosis and necrosis in MDA-MD-231 cells starting at 8.20 nM concentrations in a dose-response manner. CdS-MDx QDs biodisposition was evaluated based on an analysis of the pharmacokinetic parameters of different tissues following the administration of a single i.p. dose to rodents at several time points. We analyzed tissue images using fluorescence microscopy and tissue homogenates using spectroscopy to identify and measure CdS MDx QD content and analyze QD concentration in each tissue at predetermined time intervals. Our data clearly showed that CdS-MDx QDs were not completely cleared from in vivo systems after 360 h. Liver and kidney tissues took up the most QDs, but their Ke and MRT evidenced rapid kinetic elimination, suggesting these organs might eliminate QDs. Therefore, in an effort to further address this issue, we studied the effects of CdS-MDx QDs on embryos via an embryotoxicity assay on chicken embryos. Chicken embryos exposed to CdS-MDx QDs (0.001, 0.01, 0.1 and 1 µg/kg) in ovo for 72 h showed growth and developmental alterations during the early stage and at the end of their development in a dose-dependent manner. Current studies have also shown that CdS-MDx QDs induce embryotoxicity, affecting mainly the CNS, the neural tube and somites. The nature of the observed abnormalities suggests that these effects could be directly associated with QD concentrations affecting somitogenesis. Our results indicate that CdS-MDx QDs induce cell death in human cell lines. The pharmacokinetic properties of CdS-Mdx QDs can have therapeutic and diagnostic use but, as per current results, remain potentially harmful to embryo and fetus development. Further studies using mammalian species are required to discard additional toxic effects.